Effect of Ni3Sn4 on the Thermo-Mechanical Fatigue Life of Solder Joints in 3D IC - Zhang, Liang; Zhong, Su-Juan (Frontiers in Materials, 2021)
In this article, the 3D integration with Ni/Sn/Ni joints was conducted using transient liquid phase (TLP) bonding (250°C, 0.2 N) with different bonding time. After TLP bonding, plane-type Ni3Sn4 intermetallic compound (IMC) was observed, and when the bonding time is 180 min, complete Ni3Sn4 was found. The diffusion coefficient D was determined to be 32.4 μm2/min. Based on the finite element (FE) simulation, the results demonstrated that the shear stress and equivalent creep strain increased obviously with an increase in the IMC thickness; the results calculated show that the IMC thickness impacts the fatigue life of solder joints significantly, and the fatigue life decreases notably with an increase in the Ni3Sn4 thickness.